1969
DOI: 10.3758/bf03210651
|View full text |Cite
|
Sign up to set email alerts
|

Apparent movement and metacontrast: A note on Kahneman’s formulation

Abstract: Recently metacontrast has been described as a case of "impossible" apparent motion. Kahneman (J 967)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
80
8

Year Published

1972
1972
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(105 citation statements)
references
References 18 publications
17
80
8
Order By: Relevance
“…These results are difficult to explain on the basis of brightness summation, apparent motion, transientsustained inhibition, or contour formation processes (suppression is contourlessl). The "shaping" assumptions are also supported by the data of Growney et al (1977), andGrowney (1969) which showed that the nonmonotonicity of the metacontrast function increased with a decrease in the spatial distance between TS and MS. The extent of the spatial interaction between TS and MS conflicted with the local inhibitory considerations of metacontrast.…”
Section: Data From Metacontrast Masking Studies In Llgbtof Tbeproposesupporting
confidence: 67%
“…These results are difficult to explain on the basis of brightness summation, apparent motion, transientsustained inhibition, or contour formation processes (suppression is contourlessl). The "shaping" assumptions are also supported by the data of Growney et al (1977), andGrowney (1969) which showed that the nonmonotonicity of the metacontrast function increased with a decrease in the spatial distance between TS and MS. The extent of the spatial interaction between TS and MS conflicted with the local inhibitory considerations of metacontrast.…”
Section: Data From Metacontrast Masking Studies In Llgbtof Tbeproposesupporting
confidence: 67%
“…This is reminiscent of the debate regarding whether metacontrast masking and apparent motion reflect the same underlying mechanisms (e.g., Bischof & Di Lollo, 1995;Breitmeyer & Ganz, 1976;Di Lollo, Bischof, & Dixon, 1993;Fehrer, 1966;Kahneman, 1967;Stoper & Banffy, 1977). Although some researchers reported similarities between the two phenomena (e.g., Fehrer, 1966;Kahneman, 1967), others highlighted differences (e.g., Breitmeyer & Horman, 1981;Kolers, 1972;Stoper & Banffy, 1977;Weisstein & Growney, 1969). Breit meyer and Horman, for example, investigated the relationship between metacontrast masking and apparent motion by manipulating interstimulus interval (0-225 msec) and separation (0.14º-3.21º) between two stimuli and measuring both the magnitude of metacontrast masking and the quality of perceived motion.…”
Section: Resultsmentioning
confidence: 88%
“…This procedure assured that, except for onset and offset, the mask as well as the target were activating only sustained channels. However, under these conditions, neither of the observers reported any disappearance or decrease in the visi- (Alpern, 1953;Kolers & Rosner, 1960;Weisstein & Growney, 1969). The interaction between target-mask spatial separation and viewing eccentricity was also statistically significant for both observers' results [B.B., F(6,84)=6.5; M.K., F(6,84)=7.8; ps < .005].…”
Section: Resultsmentioning
confidence: 76%
“…They, like Weisstein and Growney (1969), showed that at stimulus spatial separations at which one obtains strong stroboscopic motion and, hence, activation of spatiotemporal sequence analyzers in a two-transient paradigm, one can fail to obtain metacontrast brightness suppression. Hence, activation of spatiotemporal sequence analyzers cannot be even a sufficient condition for obtaining metacontrast in the general case, although it may be in restricted cases.…”
Section: Resultsmentioning
confidence: 99%